Manfaat Media Flipchart dan Spanduk dalam Perilaku Kesehatan 1000 HPK di Sulawesi Tengah - Nasrul Nasrul; Zainul Zainul; Fahmi Hafid; Taqwin Taqwin (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
Flipchart and banner are communications media in behavioral change that can improve the effectiveness ofthe specific program effort of the first 1000 days of life. This study aims to prove the benefits of Flipchart media andbanners in health behavior of 1000 HPK in Central Sulawesi. The quasi-experimental design of pretest and posttest with control design is consisted of three groups of flipchart (n=32), banner (n=32) and control (n=31). TheIntervention of study is held for 6 months in Sigi, Touna and Bangkep regencies from April 15 to October 28, 2016.The population is mothers with children aged 6-23 months with 95 people sample. The data were analyzed by chisquare,paired t test and anova test. The results showed that after 6 months intervention there was an increase inthe mean behavior of 0.53±0.8 in group I with the Flipchart intervention and the mean behavior improvement of0.71±0.7 in group II with banner intervention. Increased mean behavior of intergroup I with Flipchart intervention,group II with banner and control interventions was significantly different (p=0,002). A significantly improvedbehavior is the regular weighing behavior of children. Flipcharts and beneficial banners improve the health behaviorof the first 1000 days of life in Central Sulawesi.